KEDUDUKAN HUKUM PERUSAHAAN BENTUK USAHA TETAP (PERMANENT ESTABLISHMENT) DALAM DIMENSI HUKUM PENANAMAN MODAL DI INDONESIA - Putu Ratih Prabandari (University of Udayana, 2014)
Companies with a permanent establishment is a form of a business carried on in Indonesia, carried out either by an individual or entity whose establishment was not done in Indonesia. The company with a permanent establishment differences with the concept of establishment permitted by the Investment Act. Starting from the concept, which raised the question of how the legal position of the company with a permanent establishment in the perspective of the Investment Law. The general objective of this study is an attempt to develop jurisprudence in relation to the company's legal position with a permanent establishment under the Investment Law. This normative research method, to examine the books and legal materials related to the issue under study. Companies with a permanent establishment in Indonesia is foreign investment, it is appropriate for the government is required to provide legal protection to the investors, including protecting the rights and interests of investors in investing in Indonesia. In order for them to get their rights in accordance with the laws mandated, so the investment law are expected to protect the interests of the parties who invest either directly or indirectly involved in Indonesia. Guarantee legal certainty to investors, so the investment is economically capable of generating profits for investors.